The Prevalence, Progress and Risk Factor Control of Chronic Kidney Disease in Chinese Adults With Type 2 Diabetes Mellitus in Primary Care - An, Lingwang; Yu, Qiuzhi; Tang, Hong; Li, Xianglan; Wang, Dandan; Tang, Qi; Xing, Haiyang; He, Yali; Zhao, Xiaona; Zhao, Shuhui; Lee, Yaujiunn; Lu, Juming (Frontiers in Endocrinology, 2022)
Objective: This study aimed to evaluate the prevalence of chronic kidney disease (CKD) in Chinese adults with T2DM in primary care, and the association of HbA1c, blood pressure (BP) and triglycerides (TG), i.e. ABC control at follow up (FU) with the progress and regression of CKD. Methods: A total of 5123 patients with ≥3 measurements of estimated glomerular filtration rate (eGFR), urinary albumin-to-creatinine ratio (UACR), HbA1c, BP, LDL-C and TG, and FU ≥ 12 months were included into final analysis. The presence of CKD was defined as the presence of albuminuria (UACR ≥ 30 mg/g), impaired eGFR (eGFR < 60 ml/min/1.73 m2) or both, and was categorised as low, moderate and high/very high risk. The change of CKD risk for outcome was categorised as stable (no change), progress (risk increase) and regress (risk decrease) from baseline to the last visits (LV). Results: The prevalence of CKD, impaired eGFR and albuminuria was 29.6%, 5.8% and 27.1% at baseline, with 70.4%, 20.3%, 7.0% and 2.3% of patients distributed in low, moderate, high and very high risk group. There were 3457 (67.5%), 1120 (21.8%) and 546 (10.7%) patients had CKD outcome risk stable, progressed and regressed respectively. The proportion of patients reaching targets of BP≤130/80 mmHg, HbA1c<7.5%, LDL-C<2.60 mmol/L increased from baseline to FU and LV, together with increased usage of insulin, RAS inhibitors and lipid lowering medications. After multivariable adjustment, the HbA1c<7.5% (OR: 0.66, 95%CI 0.56-0.78), TG< 1.7 mmol/L (OR: 0.81, 95%CI 0.68-0.96) at FU and BP≤130/80 mmHg at LV (OR: 0.82, 95%CI 0.70-0.95) was negatively associated with CKD outcome risk progress. Conclusion: The prevalence of CKD was high with 21.8% of patients progressing to higher CKD outcome risk at FU, attention should be paid on long term and better ABC control.